Reduced Glutathione Protects Subcellular Compartments From Pb-Induced ROS Injury in Leaves and Roots of Upland Cotton (Gossypium hirsutum L.) - Khan, Mumtaz; Samrana, Samrana; Zhang, Yi; Malik, Zaffar; Khan, Muhammad Daud; Zhu, Shuijin (Frontiers in Plant Science, 2020)
Heavy metals-based changes in the plants and their alleviation through eco-friendly agents including reduced glutathione (GSH) have been widely studied. In the present experiment, we tested the alleviatory role of reduced glutathione (GSH) in seedlings of upland cotton cultivar, TM-1 under lead (Pb) toxicity. Plants were grown in the Hoagland solution containing Pb (0 μM), Pb (500 μM), GSH (50 μM), and GSH + Pb (50 μM + 500 μM). Lead exposure exacerbated hydrogen peroxide (H2O2) and hydroxyl radical (OH•) levels, induced lipid peroxidation (MDA), and decreased the activities of catalase (CAT) and ascorbate peroxidase (APX) in the terminal and median leaves of 28-days old cotton seedlings stressed for 10 days. However, in the primary and secondary roots, CAT activity was increased but APX decreased. Similarly, peroxidase (POD) and superoxide dismutase (SOD) activities were enhanced in the median leaves but a declining trend was observed in the terminal leaves, primary roots and secondary roots. Glutathione reductase (GR) activity, ascorbic acid (AsA) contents and GSH concentrations were increased in all parts except AsA in the median leaves. Transmission electron micrographs of Pb-treated plants exhibited deformed cell wall and cell membrane, disfigured chloroplasts and irregularly shaped mitochondria in the terminal and median leaves. Further, cell membrane, mitochondria, nucleus and other cell organelles in root cells were severely affected by the Pb. Thus their identification was little bit difficult through ultramicroscopy. External GSH stabilized leaf and root ultramorphology by stabilizing cell membranes, stimulating formation of multivesicular body vesicles, and by maintaining structural integrity of other organelles. Evidently, GSH played major alleviatory role against Pb toxicity in upland cotton.